Pouring sealant and preparation method thereof
By developing a two-component silicone potting adhesive containing end-hydroxy polydimethylsiloxane, inorganic fillers, phase-change microcapsules and surface-modified hexagonal boron nitride nanosheets, the problems of salt spray and thermal management in offshore photovoltaic applications have been solved, and the anti-salt spray and heat storage and temperature control performance has been achieved, and the service life of photovoltaic modules has been extended.
Patent Information
- Application Number
- CN202411647868.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
The existing two-component silicone potting adhesives cannot meet the requirements of salt spray and thermal management in offshore photovoltaic application scenarios, resulting in reduced performance or safety risks of photovoltaic modules.
A two-component silicone potting glue was developed. Component A includes terminal hydroxy polydimethylsiloxane, inorganic fillers, phase change microcapsules and surface modified hexagonal boron nitride nanosheets. Component B includes dimethyl silicone oil, silane crosslinking agent, silane coupling agent and organotin catalyst. By optimizing component ratio and component selection, a potting glue with a uniform three-dimensional network structure is formed.
While ensuring the sealing performance of the junction box diode, this potting adhesive significantly improves the anti-salt spray performance and heat storage and temperature control performance, extending the service life of the photovoltaic module junction box in the marine environment.
Smart Images

Figure CN119505797A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer composite materials, and in particular, to a potting compound and a preparation method thereof. Background Art
[0002] With the rapid development of the photovoltaic industry, offshore photovoltaics have been valued as a solution to save land resources, but their application faces two major challenges: First, salt spray in the marine environment and corrosive ions in seawater (such as chloride ions and sodium ions) may invade and corrode the junction box diodes of photovoltaic modules, affecting their normal operation; second, as the power of photovoltaic modules increases, the heat generated by the diodes in the junction box increases, affecting the performance of photovoltaic modules. Existing two-component silicone potting glues generally cannot meet the requirements of salt spray resistance, and traditional silicone potting glues have insufficient thermal conductivity and cannot effectively dissipate heat, which may lead to performance degradation or safety risks.
[0003] Therefore, it is urgent to develop a two-component silicone potting adhesive with heat storage, temperature control and salt spray resistance for offshore photovoltaic application scenarios and thermal management of junction boxes. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems existing in the prior art to at least a certain extent.
[0005] In the first aspect of the present application, the present application proposes a potting compound. According to an embodiment of the present application, the potting compound includes: component A, wherein component A includes terminal hydroxyl polydimethylsiloxane, inorganic filler, phase change microcapsule and surface modified hexagonal boron nitride nanosheets; component B, wherein component B includes dimethyl silicone oil, silane crosslinker, silane coupling agent and organic tin catalyst. Therefore, the potting compound of the present application can effectively prevent corrosive ions in salt mist from entering the diode area of the junction box while ensuring the sealing performance of the junction box diode, thereby reducing the probability of the diode being corroded, and controlling the temperature rise of the junction box during operation through effective thermal management, thereby improving the performance and life of the junction box of the photovoltaic module in the offshore environment.
[0006] According to an embodiment of the present application, the potting glue may further include at least one of the following technical features:
[0007] According to an embodiment of the present application, the mass ratio of the terminal hydroxyl polydimethylsiloxane, the inorganic filler, the phase change microcapsule and the surface modified hexagonal boron nitride nanosheet is (40-45): (5-10): (41-46): (1-6). Thus, by making the mass ratio of the terminal hydroxyl polydimethylsiloxane, the inorganic filler, the phase change microcapsule and the surface modified hexagonal boron nitride nanosheet within the above range, the prepared potting glue can increase its salt spray resistance and heat storage temperature control performance while ensuring the sealing performance of the junction box diode, thereby improving the use effect and life of the offshore photovoltaic junction box.
[0008] According to an embodiment of the present application, the mass ratio of the dimethyl silicone oil, the silane crosslinker, the silane coupling agent and the organotin catalyst is (55-57): (37-40): (5-7): (0.1-0.2). Thus, by making the mass ratio of the dimethyl silicone oil, the silane crosslinker, the silane coupling agent and the organotin catalyst within the above range, the prepared potting glue can increase its salt spray resistance and heat storage temperature control performance while ensuring the sealing performance of the junction box diode, thereby improving the use effect and life of the offshore photovoltaic junction box.
[0009] According to an embodiment of the present application, the mass ratio of the component A to the component B is (5-5.5): 1. Thus, by making the mass ratio of the component A to the component B within the above range, the substances in the component A and the component B can fully react to form a potting compound having a uniform three-dimensional network structure.
[0010] According to an embodiment of the present application, the inorganic filler includes aluminum hydroxide or calcium carbonate. Therefore, the inorganic filler can play a role in reinforcing the potting glue and improving the flame retardant performance and thermal conductivity of the glue.
[0011] According to an embodiment of the present application, the phase change microcapsule includes a capsule core and a shell material, wherein the capsule core includes a long-chain alkane, and the shell material includes at least one of silicon dioxide, graphene oxide, and calcium carbonate. Thus, the thermal conductivity and chemical stability of the phase change microcapsule can be improved, and a larger phase change latent heat can be provided at a specific temperature, which helps to achieve efficient thermal energy storage and release.
[0012] According to an embodiment of the present application, the phase change latent heat of the phase change microcapsule is 120-150 J / g. Therefore, by making the phase change latent heat of the phase change microcapsule within the above range, the potting glue can have better heat storage and temperature control performance.
[0013] According to an embodiment of the present application, the particle size of the phase change microcapsules is 1-5 μm. Therefore, by making the particle size of the phase change capsules within the above range, it is helpful to disperse them more evenly in the potting compound, reduce agglomeration, and improve the efficiency of heat absorption of the potting compound.
[0014] According to an embodiment of the present application, the surface of the phase-change microcapsule contains a silane-modified layer, thereby improving the compatibility of the phase-change microcapsule.
[0015] According to an embodiment of the present application, the silane-modified layer includes at least one of 3-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldiethoxysilane, γ-aminopropyltriethoxysilane and γ-mercaptopropyltriethoxysilane. Thus, the compatibility of the phase-change microcapsules can be improved.
[0016] According to an embodiment of the present application, the surface-modified hexagonal boron nitride nanosheets include hexagonal boron nitride nanosheets surface-modified with 3-aminopropyltriethoxysilane, thereby improving the compatibility of the hexagonal boron nitride nanosheets.
[0017] According to the embodiment of the present application, the viscosity of the terminal hydroxyl polydimethylsiloxane is 4500-5000 cps at 20°C-30°C. Therefore, the viscosity of the terminal hydroxyl polydimethylsiloxane as the main material of the potting glue is within this range, which can provide cross-linking points, promote the cross-linking reaction, and make the potting glue achieve the expected hardening effect within a specified time, so that the potting glue has better mechanical properties.
[0018] According to an embodiment of the present application, the particle size of the inorganic filler is 1-5 μm. Therefore, by making the particle size of the inorganic filler within the above range, the inorganic filler can form a closer contact with other components, thereby improving the mechanical strength of the potting compound.
[0019] According to an embodiment of the present application, the viscosity of the dimethyl silicone oil is 800-1000 cps at 20° C.-30° C. The dimethyl silicone oil is mainly used to adjust the fluidity of the potting compound before curing. Thus, by making the viscosity of the dimethyl silicone oil within the above range, the potting compound before curing can have better fluidity.
[0020] According to an embodiment of the present application, the silane crosslinking agent includes at least one of ethyl orthosilicate, methyltrimethoxysilane and propyltrimethoxysilane. Thus, the above-mentioned silane crosslinking agent can promote and control the curing process of the potting glue, so that the potting glue forms a three-dimensional network structure.
[0021] According to an embodiment of the present application, the silane coupling agent includes at least one of N-2-aminoethyl-3-aminopropyl trimethoxysilane oligomer, 3-diethylenetriaminepropyl trimethoxysilane oligomer and γ-(methacryloyloxy)propyl trimethoxysilane oligomer. Thus, the above-mentioned types of silane coupling agents can enhance the adhesion between the potting compound and various substrates (such as metal, glass, plastic, etc.).
[0022] According to an embodiment of the present application, the organic tin catalyst includes dimethyltin dineodecanoate. Thus, the organic catalyst can accelerate the transition speed of the potting glue from liquid to solid by reducing the activation energy of the cross-linking reaction of the terminal hydroxyl polydimethylsiloxane and shorten the curing time.
[0023] According to an embodiment of the present application, the silane crosslinking agent includes the tetraethyl orthosilicate, the methyltrimethoxysilane and the propyltrimethoxysilane, and the mass ratio of the tetraethyl orthosilicate, the methyltrimethoxysilane and the propyltrimethoxysilane is (5-10): (1-1.5): (0.5-1). Thus, the curing process of the potting compound can be promoted and controlled, so that the potting compound forms a three-dimensional network structure.
[0024] According to an embodiment of the present application, the silane coupling agent includes the N-2-aminoethyl-3-aminopropyl trimethoxysilane oligomer, the 3-diethylenetriamine propyl trimethoxysilane oligomer and the γ-(methacryloxy)propyl trimethoxysilane oligomer, and the mass ratio of the N-2-aminoethyl-3-aminopropyl trimethoxysilane oligomer, the 3-diethylenetriamine propyl trimethoxysilane oligomer and the γ-(methacryloxy)propyl trimethoxysilane oligomer is 1:1:(0.5-1.5). Thus, the adhesion between the potting glue and various substrates (such as metal, glass, plastic, etc.) can be enhanced.
[0025] In the second aspect of the present application, the present application proposes a method for preparing the potting compound described in the first aspect. According to an embodiment of the present application, the method comprises: subjecting hydroxy-terminated polydimethylsiloxane, inorganic filler, phase change microcapsule and surface-modified hexagonal boron nitride nanosheets to a first mixing and a first vacuum stirring treatment to obtain the component A; subjecting dimethyl silicone oil, silane crosslinker, silane coupling agent and organic tin catalyst to a second mixing and a second vacuum stirring treatment to obtain the component B; subjecting the component A and the component B to a third mixing to obtain the potting compound. As mentioned above, the potting compound of the present application has excellent salt spray resistance and heat storage and temperature control performance. Therefore, the potting compound can be obtained quickly and easily by adopting the method of the present application.
[0026] According to an embodiment of the present application, the first vacuum stirring treatment or the second vacuum stirring treatment satisfies at least one of the following conditions: vacuum degree is -0.085MPa to -0.05MPa; time is 1 to 2h. Thus, a potting adhesive with salt spray protection and heat storage and temperature control performance can be obtained.
[0027] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0029] Figure 1 The present invention is a flow chart of preparing potting glue according to an embodiment of the present application. DETAILED DESCRIPTION
[0030] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.
[0031] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0032] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0034] In this document, the terms "include" or "comprising" are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0035] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.
[0036] In recent years, with the vigorous development of the photovoltaic industry, the land area available for photovoltaic installation has been greatly reduced. Therefore, offshore photovoltaics built on the vast sea surface have received more and more attention. At present, offshore photovoltaics have become an important part of the photovoltaic field, but this scenario also faces many challenges. On the one hand, marine salt spray and seawater contain a large number of corrosive ions, such as chloride ions and sodium ions. If these corrosive ions enter the diode area of the module junction box, they will seriously corrode the chip, affect the normal operation of the junction box, and then affect the normal use of the module. On the other hand, as the power of the photovoltaic module increases, the heat generated by the diode in the junction box when the current passes through is also increasing. If the large amount of heat generated by the diode cannot be dissipated in time, it will affect the performance of the photovoltaic module and even cause the junction box to catch fire and fail. Therefore, when sealing the junction box, it is necessary to improve its thermal management and anti-salt spray performance at sea.
[0037] Existing photovoltaic module junction boxes mostly use two-component silicone potting glue. After mixing, the two-component silicone potting glue has good fluidity, resistance to ultraviolet rays, resistance to cold and hot shocks, resistance to rain, and resistance to dirt. It is widely used in the packaging of junction box diodes. However, the two-component silicone potting glue currently used generally cannot meet the requirements of salt spray resistance. In addition, due to the low thermal conductivity of traditional silicone potting glue during protection, the heat generated when the diode is working cannot be effectively dissipated, forming local high temperature, which in turn affects the normal operation of the diode and even causes the failure of the diode and bulging of the junction box. Therefore, it is necessary to develop a two-component silicone potting glue with both heat storage and temperature control and salt spray resistance for offshore photovoltaic application scenarios and thermal management of junction boxes.
[0038] In view of this, the present application proposes a potting glue, which includes components A and B. When used for sealing the junction box diode of a photovoltaic module, it can ensure the sealing performance of the junction box while enhancing the salt spray resistance and heat storage and temperature control performance of the junction box colloid, preventing corrosive ions (such as sodium ions, chloride ions, etc.) in the salt spray from entering the junction box diode area, preventing the junction box temperature from rising sharply when the module is working, and effectively improving the performance and life of the photovoltaic module junction box in a marine environment.
[0039] Potting glue
[0040] The present application proposes a potting compound. According to an embodiment of the present application, the potting compound comprises: component A, which comprises hydroxy-terminated polydimethylsiloxane, inorganic filler, phase change microcapsule and surface-modified hexagonal boron nitride nanosheets; and component B, which comprises dimethyl silicone oil, silane crosslinking agent, silane coupling agent and organic tin catalyst.
[0041] Among them, in component A, the surface-modified hexagonal boron nitride nanosheets can play a dual role after the potting compound is cured due to their large surface area: first, they can act as a physical barrier to the corrosive ions in the salt mist that enters the potting compound, preventing these ions from penetrating into the diode area of the junction box; second, these nanosheets can adsorb the ions that have penetrated into the potting compound to their surface, thereby preventing them from further diffusion. In addition, the phase change microcapsules in component A contain phase change materials. When the ambient temperature exceeds the phase change point of the phase change material, these phase change microcapsules can absorb a large amount of heat and have the effect of regulating the temperature, thereby protecting the junction box diode from high temperature. Therefore, the potting compound of the present application has excellent salt spray resistance and heat storage and temperature control performance while ensuring the sealing performance of the junction box diode, thereby improving the performance and life of the photovoltaic module junction box in the offshore environment.
[0042] It should be noted that the "surface-modified hexagonal boron nitride nanosheets" described in the present application are modified by hydrophilic and lipophilic surfactants. The purpose of modifying the hexagonal boron nitride nanosheets with surfactants is to improve the dispersion performance of the hexagonal boron nitride nanosheets in the potting glue and the compatibility with the potting glue; wherein, the hydrophilic functional groups in the hydrophilic and lipophilic surfactants can react with the groups on the surface of the hexagonal boron nitride nanosheets and then be grafted on the surface of the hexagonal boron nitride nanosheets, and the lipophilic groups thereof can penetrate into the organic matrix, thereby serving as a bridge between the organic matrix and the hexagonal boron nitride nanosheets, so that the hexagonal boron nitride nanosheets can be better distributed in the organic matrix.
[0043] In some embodiments of the present application, the mass ratio of the hydroxy-terminated polydimethylsiloxane, the inorganic filler, the phase change microcapsule and the surface-modified hexagonal boron nitride nanosheet is (40-45): (5-10): (41-46): (1-6). For example, it can be 40:5:41:1, 45:10:44:1, 45:9:44:2, 45:10:44:1, 45:7:44:4, 45:5:44:6, 45:10:41:4, 45:5:46:4, 45:10:46:6, etc., or can be a range composed of any of the above numerical values. Therefore, by making the mass ratio of terminal hydroxyl polydimethylsiloxane, inorganic filler, phase change microcapsule and surface modified hexagonal boron nitride nanosheets within the above range, the prepared potting glue can increase its salt spray resistance and heat storage temperature control performance while ensuring the sealing performance of the junction box diode, thereby improving the use effect and life of the offshore photovoltaic junction box.
[0044] In some embodiments of the present application, the mass ratio of the dimethyl silicone oil, the silane crosslinker, the silane coupling agent and the organotin catalyst is (55-57): (37-40): (5-7): (0.1-0.2). For example, it can be 55:37:5:0.1, 55:40:5:0.1, 55:35:7:0.1, 55:37:5:0.1, 55:38:6:0.1, 57:40:7:0.2, etc., or it can be a range composed of any of the above numerical values. Therefore, by making the mass ratio of dimethyl silicone oil, silane crosslinker, silane coupling agent and organotin catalyst within the above range, the prepared potting glue can increase its salt spray resistance and heat storage temperature control performance while ensuring the sealing performance of the junction box diode, thereby improving the use effect and life of the offshore photovoltaic junction box.
[0045] In some embodiments of the present application, the mass ratio of component A to component B is (5-5.5):1. For example, it can be 5:1, 5.1:1, 5.2:1, 5.3:1, 5.4:1, 5.5:1, etc., or it can be a range composed of any of the above values. Therefore, by making the mass ratio of component A to component B within the above range, the substances in component A and component B can be fully reacted to form a potting compound with a uniform three-dimensional network structure.
[0046] In some embodiments of the present application, the inorganic filler includes aluminum hydroxide or calcium carbonate. Thus, the inorganic filler can play a role in reinforcing the potting glue and improving the flame retardant performance and thermal conductivity of the glue.
[0047] In some embodiments of the present application, the phase change microcapsule includes a capsule core and a shell material, the capsule core includes a long-chain alkane, and the shell material includes at least one of silicon dioxide, graphene oxide and calcium carbonate. As a result, the phase change microcapsule not only has good thermal conductivity and stability, but also can provide a large phase change latent heat at a specific temperature, which helps to achieve efficient thermal energy storage and release.
[0048] In some embodiments of the present application, the phase change latent heat of the phase change microcapsule is 120-150 J / g. For example, it can be 120 J / g, 125 J / g, 130 J / g, 135 J / g, 140 J / g, 145 J / g, 150 J / g, etc., or it can be a range composed of any of the above values. Therefore, by making the phase change latent heat of the phase change microcapsule within the above range, the potting glue can have better heat storage and temperature control performance.
[0049] In some embodiments of the present application, the particle size of the phase change microcapsule is 1 to 5 μm. For example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc., or it can be a range composed of any of the above values. Therefore, by making the particle size of the phase change capsule within the above range, it helps to disperse it more evenly in the potting compound, reduce agglomeration, and improve the efficiency of heat absorption of the potting compound.
[0050] In some embodiments of the present application, the surface of the phase-change microcapsule contains a silane-modified layer. The silane-modified layer includes at least one of 3-aminopropyltriethoxysilane, N-β-(aminoethyl)-γaminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldiethoxysilane, γ-aminopropyltriethoxysilane and γ-mercaptopropyltriethoxysilane. Thus, the compatibility of the phase-change microcapsule can be improved.
[0051] It should be noted that the phase change microcapsules or phase change microcapsules containing a silane modified layer described in the present application can be prepared by conventional methods, and the specific materials used can be selected by those skilled in the art according to their needs.
[0052] In some embodiments of the present application, the phase change microcapsules are silicon dioxide and graphene oxide coated n-alkane phase change microcapsules, and the preparation method thereof is as follows:
[0053] S1. Under stirring at a temperature higher than the melting point of n-alkane, a composite surfactant of n-tetradecane Tween-80 / Span-80 (n-tetradecane Tween-80:Span-80 mass ratio of 1:1) is mixed to form an oil phase;
[0054] S2. Take polyvinyl alcohol and uniformly dissolve it in deionized water to form an aqueous phase.
[0055] S3. slowly pouring the aqueous phase into the oil phase and stirring in a constant temperature water bath to form a stable emulsion containing n-alkane droplets;
[0056] S4. Slowly adding acetic acid and ethyl orthosilicate containing graphene oxide to the stable emulsion, respectively, and stirring in a constant temperature water bath to obtain a product;
[0057] S5. Wash the obtained product with anhydrous ethanol, then rinse it with deionized water, filter it, and dry it at low temperature.
[0058] In some embodiments of the present application, the phase change microcapsule containing the silane modified layer is obtained by surface modification of the phase change microcapsule, and the specific method is as follows:
[0059] S1. Weigh the phase change microcapsules prepared above and add them to N,N-dimethylformamide and stir;
[0060] S2. Deionized water and 3-aminopropyltriethoxysilane were added to S1, followed by stirring;
[0061] S3. The product obtained in S2 is washed with anhydrous ethanol and dried to obtain silane-modified phase change microcapsules.
[0062] In some embodiments of the present application, the surface-modified hexagonal boron nitride nanosheets include hexagonal boron nitride nanosheets surface-modified with 3-aminopropyltriethoxysilane. Thus, the surface-modified hexagonal boron nitride nanosheets have better compatibility and are more evenly dispersed in component A.
[0063] It should be noted that the surface-modified hexagonal boron nitride nanosheets described in the present application can be prepared by conventional methods, and the specific modified substances can be selected by those skilled in the art according to their needs.
[0064] In some embodiments of the present application, the hexagonal boron nitride nanosheets surface-modified with 3-aminopropyltriethoxysilane are prepared by the following method:
[0065] S1. Commercially available hexagonal boron nitride powder and urea were mixed together, and then the mixture was placed in an agate jar, and the mixture was mixed and ground using a planetary ball mill to obtain a white sample;
[0066] S2. Place the white sample in a crucible, heat it, then cool it to room temperature and collect the product;
[0067] S3. adding the product to an anhydrous ethanol / water mixed solution, ultrasonicating, and then centrifuging the obtained dispersion to obtain a hexagonal boron nitride nanosheet (BNNS) supernatant, and then vacuum filtering the supernatant through a microporous filter membrane, and then washing with acetone and vacuum drying to obtain amino-modified hexagonal boron nitride nanosheets;
[0068] S4. The obtained amino-modified hexagonal boron nitride nanosheets are added to a 3-aminopropyltriethoxysilane-anhydrous ethanol solution and subjected to ultrasound at room temperature;
[0069] S5. The product obtained in S4 is filtered, repeatedly washed with anhydrous ethanol, and then dried to obtain hexagonal boron nitride nanosheets modified with 3-aminopropyltriethoxysilane.
[0070] In some embodiments of the present application, the viscosity of the terminal hydroxyl polydimethylsiloxane at 20°C to 30°C is 4500 to 5000 cps. For example, the viscosity can be 4500 cps, 4600 cps, 4700 cps, 4800 cps, 4900 cps, 5000 cps, etc., or can be a range composed of any of the above values. Therefore, the viscosity of the terminal hydroxyl polydimethylsiloxane as the main material of the potting glue is within this range, which can provide cross-linking points, promote cross-linking reactions, and enable the potting glue to achieve the expected hardening effect within a specified time, so that the potting glue has better mechanical properties.
[0071] In some embodiments of the present application, the particle size of the inorganic filler is 1 to 5 μm. For example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc., or it can be a range composed of any of the above values. Therefore, by making the particle size of the inorganic filler within the above range, the inorganic filler can form a closer contact with other components, thereby improving the mechanical strength of the potting compound.
[0072] In some embodiments of the present application, the viscosity of the dimethyl silicone oil at 20°C to 30°C is 800 to 1000 cps. For example, it can be 800 cps, 850 cps, 900 cps, 950 cps, 1000 cps, etc., or can be a range composed of any of the above values. Dimethyl silicone oil is mainly used to adjust the fluidity of the potting glue before curing. Therefore, by making the viscosity of the dimethyl silicone oil within the above range, the potting glue before curing can have better fluidity.
[0073] In some embodiments of the present application, the silane crosslinking agent includes at least one of ethyl orthosilicate, methyltrimethoxysilane and propyltrimethoxysilane. Thus, the above-mentioned silane crosslinking agent can promote and control the curing process of the potting compound, so that the potting compound forms a three-dimensional network structure.
[0074] In some embodiments of the present application, the silane coupling agent includes at least one of N-2-aminoethyl-3-aminopropyl trimethoxysilane oligomer, 3-diethylenetriaminopropyl trimethoxysilane oligomer and γ-(methacryloyloxy)propyl trimethoxysilane oligomer. Thus, the above-mentioned types of silane coupling agents can enhance the adhesion between the potting compound and various substrates (such as metal, glass, plastic, etc.).
[0075] In some embodiments of the present application, the organic tin catalyst includes dimethyltin dineodecanoate. Thus, the organic catalyst can accelerate the transition speed of the potting glue from liquid to solid by reducing the activation energy of the cross-linking reaction of the hydroxyl-terminated polydimethylsiloxane and shorten the curing time.
[0076] In some embodiments of the present application, the silane crosslinking agent includes tetraethyl orthosilicate, methyltrimethoxysilane and propyltrimethoxysilane, and the mass ratio of tetraethyl orthosilicate, methyltrimethoxysilane and propyltrimethoxysilane is (5-10): (1-1.5): (0.5-1). For example, it can be 5:1:0.5, 5:1.5:0.5, 6:1:1, 8:1.2:0.8, 10:1.5:0.8, 10:1.5:1, etc., or it can be a range composed of any of the above numerical values. Thus, by making the mass ratio of tetraethyl orthosilicate, methyltrimethoxysilane and propyltrimethoxysilane within the above range, the curing process of the potting glue can be promoted and controlled, so that the potting glue forms a three-dimensional network structure.
[0077] In some embodiments of the present application, the silane coupling agent includes N-2-aminoethyl-3-aminopropyl trimethoxysilane oligomer, 3-diethylenetriamine propyl trimethoxysilane oligomer and γ-(methacryloyloxy)propyl trimethoxysilane oligomer, and the mass ratio of the N-2-aminoethyl-3-aminopropyl trimethoxysilane oligomer, 3-diethylenetriamine propyl trimethoxysilane oligomer and γ-(methacryloyloxy)propyl trimethoxysilane oligomer is 1:1:(0.5-1.5). For example, it can be 1:1:0.5, 1:1:0.8, 1:1:1, 1:1:1.2, 1:1:1.5, etc., or it can be a range composed of any of the above numerical values. Therefore, by making the mass ratio of N-2-aminoethyl-3-aminopropyltrimethoxysilane oligomer, 3-diethylenetriaminopropyltrimethoxysilane oligomer and γ-(methacryloyloxy)propyltrimethoxysilane oligomer within the above-mentioned range, the adhesion between the potting compound and various substrates (such as metal, glass, plastic, etc.) can be enhanced.
[0078] Method for preparing potting glue
[0079] The present application proposes a method for preparing the above-mentioned potting glue. According to the embodiments of the present application, reference Figure 1 , the method comprising:
[0080] S100: First Hybrid
[0081] In this step, terminal hydroxyl polydimethylsiloxane, inorganic filler, phase change microcapsule and surface modified hexagonal boron nitride nanosheets are first mixed to obtain a first mixed product.
[0082] S200: First vacuum stirring process
[0083] In this step, the first mixed product is subjected to a first vacuum stirring treatment to obtain component A.
[0084] In some embodiments of the present application, the vacuum degree of the first vacuum stirring process is -0.085MPa to -0.05MPa. For example, it can be -0.085MPa, -0.08MPa, -0.075MPa, -0.07MPa, -0.06MPa, -0.05MPa, etc., or it can be a range composed of any of the above values. Therefore, by making the vacuum degree within the above range, the mixing of air can be reduced and the formation of bubbles during the stirring process can be avoided.
[0085] In some embodiments of the present application, the first vacuum stirring treatment time is 1 to 2 hours. For example, it can be 1 hour, 1.2 hours, 1.5 hours, 1.8 hours, 2 hours, etc., or can be a range of any of the above values. Therefore, by making the time within the above range, it is helpful to uniformly mix the various components and ensure the consistency and stability of component A.
[0086] S300: Second Hybrid
[0087] In this step, dimethyl silicone oil, a silane crosslinking agent, a silane coupling agent and an organic tin catalyst are mixed for a second time to obtain a second mixed product.
[0088] S400: Second vacuum stirring process
[0089] In this step, the second mixed product is subjected to a second vacuum stirring treatment to obtain component B.
[0090] In some embodiments of the present application, the vacuum degree of the second vacuum stirring process is -0.085MPa to -0.05MPa. For example, it can be -0.085MPa, -0.08MPa, -0.075MPa, -0.07MPa, -0.06MPa, -0.05MPa, etc., or it can be a range composed of any of the above values. Therefore, by making the vacuum degree within the above range, the mixing of air can be reduced and the formation of bubbles during the stirring process can be avoided.
[0091] In some embodiments of the present application, the second vacuum stirring treatment time is 1 to 2 hours. For example, it can be 1 hour, 1.2 hours, 1.5 hours, 1.8 hours, 2 hours, etc., or it can be a range of any of the above values. Therefore, by making the time within the above range, it is helpful to uniformly mix the various components and ensure the consistency and stability of component B.
[0092] S500: Third Hybrid
[0093] In this step, the component A obtained by the first vacuum stirring treatment and the component B obtained by the second vacuum stirring treatment are mixed for the third time to obtain the potting glue.
[0094] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the document in this area or the product specification are used. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.
[0095] Example 1
[0096] 1. Preparation of Phase Change Microcapsules
[0097] The phase change microcapsules used in this application are silicon dioxide / graphene oxide coated n-alkane phase change microcapsules, and the specific preparation method is as follows:
[0098] (1) at a temperature higher than the melting point of n-alkane and under stirring at 1000 rpm, 10 g of n-tetradecane and 0.8 g of a composite surfactant of Tween-80 and Span-80 (Tween-80: Span-80 mass ratio is 1:1) were mixed uniformly to form an oil phase;
[0099] (2) Take 1.5 g of polyvinyl alcohol and uniformly dissolve it in 100 mL of deionized water to form an aqueous phase.
[0100] (3) slowly pouring the aqueous phase into the oil phase and stirring at 1000 rpm in a constant temperature water bath for 30 min to form a stable emulsion containing n-alkane droplets;
[0101] (4) slowly adding 0.2 g (15 wt%) of acetic acid and 10 g of ethyl orthosilicate containing 15% graphene oxide to the stable emulsion, respectively, and stirring the polymerization reaction at a speed of 800 rpm in a constant temperature water bath for 2 h to obtain the product;
[0102] (5) The obtained product is washed with anhydrous ethanol for 2-3 times, then washed with deionized water, filtered, and dried at low temperature to obtain phase change microcapsules.
[0103] 2. Surface modification of phase change microcapsules
[0104] The phase change microcapsules in 1 are surface modified to improve the compatibility of the phase change microcapsules. The specific steps are as follows:
[0105] (1) Weigh 0.6 g of the phase change microcapsules prepared above and add them to 50 ml of N,N-dimethylformamide, and disperse them at a stirring speed of 1200 rpm for 1 h;
[0106] (2) adding 20 ml of deionized water and 500 ml of 3-aminopropyltriethoxysilane to (1), and mixing and stirring at 800 rpm for 1.5 h;
[0107] (3) The product obtained in (2) is washed with anhydrous ethanol for 3 to 4 times, and then dried to obtain silane-modified phase change microcapsules.
[0108] 3. Preparation of surface-modified hexagonal boron nitride nanosheets
[0109] The surface-modified hexagonal boron nitride nanosheets used in this application are 3-aminopropyltriethoxysilane surface-modified hexagonal boron nitride nanosheets, and the specific preparation method is as follows:
[0110] (1) Commercially available hexagonal boron nitride powder and urea were mixed at a mass ratio of 1:4, and then the mixture was placed in an agate jar and ground using a planetary ball mill at a speed of 3000 rpm for 6 hours to obtain a white sample;
[0111] (2) placing the white sample obtained in step (1) into a crucible, heating it to 600° C. at a heating rate of 2° C. / min, maintaining it for 2 h, then cooling it to room temperature, and collecting the product;
[0112] (3) adding the product obtained in step (2) to a mixed solution of anhydrous ethanol and water (the volume ratio of anhydrous ethanol to water is 2:1), ultrasonically dispersing at 25°C for 1 hour, and then centrifuging the obtained dispersion at 3000 r / min for 30 minutes to obtain a hexagonal boron nitride nano (BNNS) supernatant, and then vacuum filtering the supernatant through a 0.20 μm microporous filter membrane, followed by washing with acetone, and vacuum drying at 75°C for 12 hours to obtain amino-modified hexagonal boron nitride nanosheets;
[0113] (4) adding the amino-modified hexagonal boron nitride nanosheets prepared in the above step (3) into a 3-aminopropyltriethoxysilane-anhydrous ethanol solution (the volume ratio of 3-aminopropyltriethoxysilane to anhydrous ethanol is 1:10) and ultrasonically dispersing at room temperature for 3 hours;
[0114] (5) The product obtained in step (4) was filtered and repeatedly washed with anhydrous ethanol for 5 times, and then dried at 70° C. for 8 h to obtain hexagonal boron nitride nanosheets modified with 3-aminopropyltriethoxysilane.
[0115] Example 2
[0116] The specific method for preparing the potting compound is as follows:
[0117] (1) Preparation of component A: Weigh 45 parts by mass of terminal hydroxyl polydimethylsiloxane (viscosity at 25°C is 4800 cps), 10 parts by mass of aluminum hydroxide, 44 parts by mass of the surface-modified phase change microcapsules prepared in Example 1, and 1 part by mass of hexagonal boron nitride surface-modified with 3-aminopropyltriethoxysilane prepared in Example 1, add them together into a planetary mixer, stir evenly under vacuum in the planetary mixer at a vacuum degree of -0.07 MPa, and discharge the mixture after 1.5 hours for standby use.
[0118] (2) Preparation of component B: Weigh 55.9 parts by mass of dimethyl silicone oil, 30.4 parts by mass of tetraethyl orthosilicate, 4.6 parts by mass of methyltrimethoxysilane, 3 parts by mass of propyltrimethoxysilane, 2 parts by mass of N-2-aminoethyl-3-aminopropyltrimethoxysilane oligomer, 2 parts by mass of 3-diethylenetriaminopropyltrimethoxysilane oligomer, 2 parts by mass of γ-(methacryloyloxy)propyltrimethoxysilane oligomer, and 0.1 parts by mass of dimethyltin dineodecanoate, add them into a planetary mixer in that order, stir them evenly under vacuum in the planetary mixer at a vacuum degree of -0.07 MPa, and discharge the mixture after 1.5 hours for standby use.
[0119] (3) Mix 5 parts by mass of component A and 1 part by mass of component B to obtain a potting compound.
[0120] The preparation methods of Examples 3 to 8 are the same as those of Example 2, except that the addition amounts of the components in component A in Examples 3 to 8 are different, as shown in Table 1.
[0121] The preparation method of Comparative Example 1 is the same as that of Example 2, except that no phase change microcapsules are added to component A in Comparative Example 1.
[0122] The preparation method of Comparative Example 2 is the same as that of Example 2, except that no surface-modified hexagonal boron nitride nanosheets are added to component A in Comparative Example 2.
[0123] The preparation method of Comparative Example 3 is the same as that of Example 2, except that component A in Comparative Example 3 is composed of terminal hydroxyl polydimethylsiloxane and aluminum hydroxide, and the viscosity of the terminal hydroxyl polydimethylsiloxane at 25° C. is 3000-3500 cps.
[0124] Table 1
[0125]
[0126]
[0127] Performance Testing
[0128] Curing hardness (GB / T 531.1-2008), thermal conductivity (GB / T11205), tensile strength (GB / T 528-2009), phase change enthalpy (differential scanning calorimetry);
[0129] The sample preparation and experimental process of salt spray resistance test are as follows: the test samples are all 150mm×100mm×1mm steel plates, the surface is degreased with solvent and polished with sandpaper, the potting glue of this application and the ordinary two-component potting glue are applied on the steel plate, and the mixed two-component potting glue is evenly applied on the front and back surfaces and the side of the steel plate using a thickness controller, so that the potting glue completely covers the steel plate, and the thickness of the potting glue is controlled at (150±10)μm. After curing for 14 days under standard test conditions (temperature (23±2)℃, relative humidity (50±5)%), the salt spray test is carried out, and attention is paid to ensure that the potting glue is completely cured. The salt spray test is carried out in accordance with GB / T 1771-2007.
[0130] The performance of the potting glue of Examples 2 to 8 and Comparative Examples 1 to 3 was tested, and the test results are shown in Table 2:
[0131] Table 2
[0132]
[0133] It can be seen from Examples 2 to 8 and Comparative Examples 2 and 3 that the potting glue using surface-modified hexagonal boron nitride nanosheets as fillers has no obvious difference in curing hardness and tensile strength compared to Comparative Examples 2 and 3 (without adding surface-modified hexagonal boron nitride nanosheets), indicating that the conventional performance of the potting glue will not be greatly affected when the surface-modified hexagonal boron nitride nanosheets are used as fillers. However, when the surface-modified hexagonal boron nitride nanosheets are used as fillers, they have good anti-salt spray performance. This is because the surface of the surface-modified hexagonal boron nitride nanosheets has a variety of functional groups, which are easier to disperse, and after being surface treated with dopamine, a large number of amino groups will exist on its surface, making it more compatible with the base glue and can be evenly dispersed in the base glue. After being evenly dispersed in the base glue, a large-area protective layer can be formed with its sheet-like shape, thereby blocking the invasion of corrosive medium ions in salt spray, achieving the effect of anti-salt spray, and its anti-salt spray effect will be enhanced with the increase of the content of the surface-modified hexagonal boron nitride nanosheets.
[0134] In addition, it can be seen from Examples 2 to 8 and Comparative Examples 1 and 3 that the use of silicon dioxide and graphene oxide coated phase change microcapsules as fillers will not have a significant impact on the mechanical properties of the potting compound. However, when phase change microcapsules are used as fillers, the enthalpy value of the potting compound is much higher than that of ordinary photovoltaic potting compounds, and has better heat storage and temperature control functions.
[0135] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0136] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A potting glue, characterized in that: include: Component A, comprising hydroxy-terminated polydimethylsiloxane, inorganic filler, phase change microcapsules and surface-modified hexagonal boron nitride nanosheets; Component B includes dimethyl silicone oil, a silane crosslinking agent, a silane coupling agent and an organic tin catalyst.
2. The potting compound according to claim 1, characterized in that: The mass ratio of the terminal hydroxyl polydimethylsiloxane, the inorganic filler, the phase change microcapsule and the surface modified hexagonal boron nitride nanosheet is (40-45):(5-10):(41-46):(1-6); And / or, the mass ratio of the dimethyl silicone oil, the silane cross-linking agent, the silane coupling agent and the organic tin catalyst is (55-57):(37-40):(5-7):(0.1-0.2).
3. The potting compound according to claim 2, characterized in that: The mass ratio of the component A to the component B is (5-5.5):1; And / or, the inorganic filler includes aluminum hydroxide or calcium carbonate.
4. The potting compound according to claim 3, characterized in that: The phase-change microcapsule comprises a capsule core and a shell material, wherein the capsule core comprises a long-chain alkane, and the shell material comprises at least one of silicon dioxide, graphene oxide and calcium carbonate; And / or, the phase change latent heat of the phase change microcapsule is 120-150 J / g; And / or, the particle size of the phase change microcapsules is 1 to 5 μm; And / or, the surface of the phase change microcapsule contains a silane-modified layer, optionally, the silane-modified layer includes at least one of 3-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldiethoxysilane, γ-aminopropyltriethoxysilane and γ-mercaptopropyltriethoxysilane.
5. The potting compound according to claim 1, characterized in that: The surface-modified hexagonal boron nitride nanosheets include hexagonal boron nitride nanosheets surface-modified with 3-aminopropyltriethoxysilane.
6. The potting compound according to claim 3, characterized in that: The viscosity of the terminal hydroxyl polydimethylsiloxane at 20°C to 30°C is 4500 to 5000 cps; And / or, the particle size of the inorganic filler is 1 to 5 μm; And / or, the viscosity of the dimethyl silicone oil at 20° C. to 30° C. is 800 to 1000 cps.
7. The potting compound according to claim 3, characterized in that: The silane crosslinking agent includes at least one of ethyl orthosilicate, methyltrimethoxysilane and propyltrimethoxysilane; And / or, the silane coupling agent includes at least one of N-2-aminoethyl-3-aminopropyltrimethoxysilane oligomer, 3-diethylenetriaminopropyltrimethoxysilane oligomer and γ-(methacryloyloxy)propyltrimethoxysilane oligomer; And / or, the organotin catalyst comprises dimethyltin diceneodecanoate.
8. The potting compound according to claim 7, characterized in that: The silane crosslinking agent includes the tetraethyl orthosilicate, the methyltrimethoxysilane and the propyltrimethoxysilane, and the mass ratio of the tetraethyl orthosilicate, the methyltrimethoxysilane and the propyltrimethoxysilane is (5-10):(1-1.5):(0.5-1); And / or, the silane coupling agent includes the N-2-aminoethyl-3-aminopropyltrimethoxysilane oligomer, the 3-diethylenetriaminopropyltrimethoxysilane oligomer and the γ-(methacryloyloxy)propyltrimethoxysilane oligomer, and the mass ratio of the N-2-aminoethyl-3-aminopropyltrimethoxysilane oligomer, the 3-diethylenetriaminopropyltrimethoxysilane oligomer and the γ-(methacryloyloxy)propyltrimethoxysilane oligomer is 1:1:(0.5-1.5).
9. A method for preparing the potting compound according to any one of claims 1 to 8, characterized in that: include: The terminal hydroxyl polydimethylsiloxane, the inorganic filler, the phase change microcapsule and the surface-modified hexagonal boron nitride nanosheets are subjected to a first mixing and a first vacuum stirring treatment to obtain a component A; Performing a second mixing and a second vacuum stirring treatment on dimethyl silicone oil, a silane crosslinking agent, a silane coupling agent and an organic tin catalyst to obtain a component B; The component A and the component B are mixed for the third time to obtain the potting glue.
10. The method according to claim 9, characterized in that The first vacuum stirring process or the second vacuum stirring process satisfies at least one of the following conditions: Vacuum degree: -0.085MPa~-0.05MPa; The time is 1 to 2 hours.
Citation Information
Cited By
Packaging material and preparation method and application thereof
CN121319860A
Optical sensor package structure and electronic device
US12388064B2
Optical sensor package structure and electronic device
US20230246012A1